Pemanfaatan Sampah Pasar Sebagai Media Budidaya Cacing Tanah Eisenia Fetida Untuk Meningkatkan Kokon dan Biomassa - Mashur Mashur (Program Studi Pendidikan Geografi Universitas Hamzanwadi, 2020)
Market waste management is still a problem that cannot be solved until now. One effort that can be done is to utilize market organic waste as a media for cultivating earthworms Eisenia fetida. To find out the influence of the use of market waste as a cultivation medium to increase cocoon and biomass production, a research was carried out using a Completely Randomized Design with five treatments with three replications. Research findings show that market waste utilization has a significant effect (P 0.05) on cocoon and biomass production. The 50% mixture (market waste + cattle feces) is the best medium in producing the most cocoon 207.7 grains/nest box while the 50% mixture (market waste + horse feces) is the best medium in producing the most biomass of 1,362 animals weighing 47.9 grams/nest box. The conclusion is that market organic waste used as the best medium to increase the production of Einesia foetida cocoon and biomass when mixed with cow and horse feces.